The Role of the National Human Right in Dealing with the Widows Social Exclusion in Anambra State, 2010 – 2020 - Okezie Easther Chiamaka; Joseph Bamidele; Paul Anyaogu (MultiTech Publisher, 2023)
Across different cultures in Nigeria, there exist harmful traditional widowhood practices which have attracted the attention of the global struggle in general on violence against women. This study employed the survey research method. Questionnaires were administered to 400 respondents. The findings among others includes: there is existence of social exclusion in Nigeria and this grossly affects the Nigerian democracy and the fundamental human rights; Widows in Nigeria face lot of challenges and ill treatment; The National Human Right Commission plays active role in addressing widow’s right; In as much as the NHRC tries in their fight against widows’ right violation, they faces several challenges. Base on the findings, the work recommends among others that; The federal government should look into all level of social exclusion in Nigeria and develop policies and programmes that will help in addressing these social irregularities in the country; The government should accommodate the widows through policies and programmes that will help to empower the widows in Nigeria.The federal government should ensure independence of the NHRCN so that the commission can perform actively without fear and favour, etc.